Hybrid photovoltaic thermal systems : Present and future feasibilities for industrial and building applications - Samykano, Mahendran (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The growing demands of modern life, industrialization, and technological progress have significantly increased energy requirements. However, this heightened need for energy has raised concerns about its impact on the environment and the rising costs associated with it. Therefore, the engineering sector is actively seeking sustainable and cost-effective energy solutions. Among the promising innovations in solving the problem is the photovoltaic thermal system (PVT), which aims to capture electrical and thermal energy from solar radiation. Despite its potential, the application of PVT systems is currently limited due to the unpredictable nature of solar energy and the absence of efficient thermal energy storage capabilities. To address these challenges, researchers have explored the use of phase change materials and nano-improved phase change materials (NEPCMs) to optimize energy extraction from solar systems. By incorporating these materials, the PVT system can maximize energy utilization. This article provides a comprehensive overview of the potential applications of PVT techniques in both industrial and building settings. It also offers a detailed assessment of their commercial and environmental aspects. The research findings highlight several advantages of PVT systems, including reduced electricity consumption, efficient utilization of cooling and heating loads during off-peak periods, improved temperature stability, and enhanced thermal comfort. Furthermore, the integration of NEPCMs in PVT systems has demonstrated superior thermal performance, enabling 8.3% more heat energy storage during charging and 25.1% more heat energy release during discharging. Additionally, the implementation of solar-assisted combined heating and power systems showed the potential to prevent the emission of 911 tons of CO2 per year compared to conventional PV systems. These systems offer a promising pathway towards mitigating environmental impacts while meeting energy demands. Overall, this review article serves as a valuable resource for fellow researchers by providing detailed insights into the viability of PVT systems for various applications in the industrial and building sectors.